Implementasi Algoritme Dijkstra pada Webgis untuk Pencarian Lokasi SPBU di Kota Malang - Mega Yuda Rukmana; Fatwa Ramdani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Malang is the second largest city in East Java, which has an annual increase of 9.98% or 81.934 people. Immigrants (visitors) as new residents are difficult to find gas stations as needed in the middle of traffic and lack of information about the location and the shortest route that can be taken. To overcome this problem, this research uses Geographic Information System (GIS) application based on web that can channel information about the path that can be taken to speed up the searching process by following the shortest route path using Dijkstra algorithm that has been produced. The methodology used in this research is literature study, data collection, application of Shorttest Bastpath, WebGIS development using Dijkstra Algorithm to calculate the shortest route, test and analysis of the application that has been built, and conclude the research result. The nearest route information can be obtained by using Dijkstra Algorithm to determine the closest distance of SPBU in Malang City. Recommendation to the visitor is done by giving checklist of SPBU feature based on survey result to 26 SPBU in Malang City combined with Dijkstra Algorithm. Applying Bastpath to Dijkstra's Algorithm by digitizing the provincial or national path (protocol road) in overlay with googlemap with roadmap map type obtained good accuracy.